HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN PERILAKU IBU POST PARTUM DALAM PERAWATAN BAYI SELAMA PANDEMI COVID-19 DI WILAYAH KERJA PUSKESMAS NGALI - Tri Yubiah; Nurbaety Nurbaety (LPPM - Universitas Muhammadiyah Banjarmasin, 2022)
The independent variable is family support, while the dependent variable is the behavior of postpartum mothers in caring for babies during the COVID-19 pandemic. This study aims to determine the relationship between family support and postpartum mother's behavior in caring for babies during the COVID-19 pandemic in the working area of the Ngali Health Center. The research design used correlation analytic, with a total sample of 140 respondents according to the calculation of the nominal ordinal correlation analytic sample size. The results of the study show that family support plays an important role in caring for babies during the COVID-19 pandemic, as seen in the results of the SPSS calculation showing that the correlation coefficient value is 0.381 while the confidence alpha is 0.05. so that there is a correlation between the two variables. It is hoped that with good family support, postpartum mothers can take good care of their babies during the current pandemic. With good baby care, they will grow up healthy and can become the next generation of a strong and quality nation